The Dramaturgies of Volumetric Capture - Miller, Lee; Whalley, Joanne 'Bob' (Mimesis Journal, 2024)
The article explores the potential of emerging volumetric and capturing technologies in reshaping the documentation, archiving, and accessibility of performance work. It discusses how these technologies can impact the relationship between live and mediated experiences, and their possible effects on dramaturgical strategies in ephemeral, process-driven performance practices. It also acknowledges the challenges in documenting live performances and the intrinsic gap between the source and its document, amplified by the digital medium. The article emphasizes the ephemerality and inevitable obsolescence of the archive.